دور أعوان المحاسبة العمومية في فعالية تنفيذ ميزانية الجماعات المحلية دراسة تحليلية لتنفيذ ميزانية البلدية - بيصار, عبد المطلب (جامعة الوادي - University of Eloued, 2021)
: In order to achieve effectiveness in managing public budgets, and to embody the state’s strategy of working to increase resources and reduce expenditures, this study came with the aim of highlighting the role of public accounting agents in the effective implementation of the budget of local authorities, and to achieve this in practice according to a scientific methodology, an analytical study was carried out that included Mechanisms for implementing the municipal budget, and data was collected through laws and executive decrees that govern the implementation of these budgets in addition to the interview. In the field of oversight of its implementation, and one of the most prominent findings of the study is that there is an effective role for the disbursement commander represented in the President of the National People’s Assembly in the field of revenue collection and payment of expenditures, and the role of the public accountant and financial controller is no less important than that, given that they also play a supervisory role in implementation. The study recommended the necessity of training those who are in charge of spending before they are appointed so that public accounting procedures are respected in the field of budget execution general
The role of public accounting agents in the effective implementation of the Analytical study for the implementation of the municipal budget of local authorities budget
مقال
Keywords: الميزانية؛ الجماعات المحلية؛ البلدية؛ أعوان المحاسبة العمومية؛ الآمر بالصرف؛ المحاسب العمومي; Local groups; Municipal; public accountants; ordering disbursement; public accountant